Resolving the characteristics of morphotropic phase boundary in the (1-x) Pb (Fe1/2 Nb1/2) O3 -x PbTiO3 system: A combined dielectric and synchrotron x-ray diffraction study - Singh S.P.; Pandey D.; Yoon S.; Baik S.; Shin N. (My University, 2025)
Frequency dependent dielectric studies on the mixed system (1-x) Pb (Fe1/2 Nb1/2) O3 -x PbTiO3 reveal contributions from the electrodes, grain boundaries, and grains. It is shown that the intrinsic value of the dielectric permittivity coming only from the grains peaks at x=0.08. Analysis of synchrotron x-ray diffraction profiles using the Rietveld technique shows that this peaking is linked with a monoclinic to tetragonal morphotropic phase transition in the multiferroic system. © 2008 American Institute of Physics.